Latent Risk Intrahepatic Cholangiocarcinoma Susceptible to Adjuvant Treatment After Resection: A Clinical Deep Learning Approach - Jeong, Seogsong; Ge, Yang; Chen, Jing; Gao, Qiang; Luo, Guijuan; Zheng, Bo; Sha, Meng; Shen, Feng; Cheng, Qingbao; Sui, Chengjun; Liu, Jingfeng; Wang, Hongyang; et al. (Frontiers in Oncology, 2020)
Background: Artificial Intelligence (AI) frameworks have emerged as a novel approach in medicine. However, information regarding its applicability and effectiveness remain unclear in a clinical prognostic factor setting. Methods: The AI framework was derived from a pooled dataset of intrahepatic cholangiocarcinoma (ICC) patients from 3 clinical centers (n = 1421) by applying the TensorFlow deep learning algorithm to Cox-indicated 4 pathologic, 6 serologic, and 2 etiologic factors; this algorithm was validated using a dataset of ICC patients from an independent clinical center (n = 234). The model was compared to the commonly used staging system (American Joint Committee on Cancer; AJCC) and methodology (Cox regression) by evaluating the brier score (BS), integrated discrimination improvement (IDI), net reclassification improvement (NRI), and area under curve (AUC) values. Results: The framework (BS, 0.17; AUC, 0.78) was found to be more accurate than the AJCC stage (BS, 0.48; AUC, 0.60; IDI, 0.29; NRI, 11.85; P < 0.001) and the Cox model (BS, 0.49; AUC, 0.70; IDI, 0.46; NRI, 46.11; P < 0.001). Furthermore, hazard ratios greater than 3 were identified in both overall survival (HR; 3.190; 95% confidence interval [CI], 2.150-4.733; P < 0.001) and disease-free survival (HR, 3.559; 95% CI, 2.500-5.067; P < 0.001) between latent risk and stable groups in validation. In addition, the latent risk subgroup was found to be significantly benefited from adjuvant treatment (HR, 0.459; 95% CI, 0.360-0.586; P < 0.001). Conclusions: The AI framework seems promising in prognostic estimation and stratification of susceptible individuals for adjuvant treatment in patients with ICC after resection. Future prospective validations are needed for the framework to be applied in clinical practice.